“I Have Guys Call Me and Say ‘I Can’t Be the Victim of Domestic Abuse’”: Exploring the Experiences of Telephone Support Providers for Male Victims of Domestic Violence and Abuse - Hine, Benjamin; Bates, Elizabeth A.; Wallace, Sarah (Journal of interpersonal violence, 2022)
While previous studies have begun to provide evidence on the experiences of male victims of domestic violence and abuse (DVA), current understanding in this area is still limited, and subject to narrow methods of inquiry. Moreover, little is known regarding the challenges of providing support to men in abusive relationships, and how barriers to effective service engagement are experienced by both men and service practitioners. This is an important area for exploration, as the gender-specific experiences and needs of men have been historically overlooked within academic research and service provision. The present study therefore had two principal aims: first, to provide more detailed information regarding the nature and context of abuse toward, and help-seeking experiences of, male victims, and second, to explore the experiences of those supporting abused men. Semi-structured interviews were conducted with four call handlers at a U.K. domestic abuse charity supporting male victims. Transcribed interviews were subjected to thematic analysis, revealing a superordinate theme of stereotypes and expectations of men which affected all the other three overarching and eight subthemes, including those detailing the range and severity of abuse suffered, the role of family and friends, barriers to reporting for abused men, and challenges in supporting them. Implications for services working with male victims of DVA are discussed: centered around the need for recognition, increased awareness, increased resourcing, and the provision of gender-inclusive services catering for the gender-specific needs of men.